PD-1/PD-L1 pathway in breast cancer - Schütz, Florian; Stefanovic, Stefan; Mayer, Luisa; Au, Alexandra von; Domschke, Christoph; Sohn, Christof (Oncology research and treatment, 2017)
The programmed cell death-1 receptor (PD-1) is an immune checkpoint inhibitor which is expressed on the surface of immune effector cells. It is activated mainly by PD-L1 which can be expressed by all human cells. The PD-1/PD-L1 pathway plays a subtle role in maintaining peripheral T-lymphocyte tolerance and regulating inflammation. In cancer, the expression of PD-L1 seems to be one of the major immune escape mechanisms. Many studies have shown efficacy of blocking PD-1 or PD-L1 with specific antibodies like pembrolizumab or atezulizumab. In breast cancer, potential response was demonstrated in metastatic triple-negative breast cancers.
Gesehen am 20.04.2018